PENYULUHAN HUKUM TENTANG PENCEGAHAN KDRT BERBASIS PENGABDIAN KEPADA MASYARAKAT DENGAN KEGIATAN KULIAH KERJA LAPANG (KKLP) - Nur Insani,; Asdar Arti,; Upik Mutiara, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
This service aims as follows: a. Able to provide understanding to the community about the importance of a family that is truly obedient and aware of the law. b. Increase legal awareness for the community so that they are no longer victims of domestic violence (KDRT). c. Provide knowledge to the public about the steps that must be taken if they become victims of domestic violence. The method of implementing community service activities is by delivering material, conducting discussions and asking questions. The results obtained from these service activities have succeeded in contributing and changing public perceptions, namely an increase in knowledge and understanding of the importance of preventing domestic violence. In addition, with these service activities, it is hoped that they will have value benefits for the community, so that they can participate in disseminating information related to the prevention of domestic violence to the wider community. The target audience in this activity were local residents of Ilomata Village, Tibawa District, Gorontalo Regency, Gorontalo Province, totaling 25 participants.